Understanding Faculty Engagement in Assessment through Feedback and Dialogues: A Mixed Methods Approach - Robert W. Elliott (Institute of Advanced Engineering and Science, 2018)
The literature indicates faculty members' beliefs and attitudes toward assessment are crucial to the successful implementation of assessment. However, few empirical studies have examined the culture of assessment among faculty members. The intent of this single-level mixed methods case study is to identify the factors and examine how these factors influence faculty members' perceptions, attitudes, and their engagement in assessment activities by studying the case of a public teaching intensive university in the Southwest region of the U.S. An online survey and asynchronous focus group interviews are used. The implications for institutional policy making and professional development are discussed, based on the findings.